Effects of process parameters on spray drying of recombinant bromelain - Muntari, Bala; Amid, Azura; Jami, Mohammed Saedi; Mel, Maizirwan; Mohd. Salleh, Hamzah (2013)
Bromelain is a plant protease with diverse industrial, analytical and pharmacological uses. This research work is aimed at evaluating the effects of some process parameters (inlet temperature, pump and aspirator settings) on spray drying of recombinant bromelain using full factorial design of experiments. The experiments were conducted in Buchi B-290 mini spray dryer using maltodextrin as carrier agent. The results obtained revealed that the interaction and linear coefficients wer e statistically significant coupled with existence of good conformity between the experimental and the theoretical values predicted by the model. The precise optimum conditions obtained (aspirator setting, 90 (%); inlet temperature, 110 ºC; and pump setting, 12.5 %) generated the maximum activity of 78.08±0.07 U/ml (equivalent to residual activity of about 92.64±0.09) for the spray dried recombinant bromelain. This implies that the study has effectively produced viable and well formulated spray dried recombinant bromelain under optimized conditions.